Design of a strategic management plan for the fishery sector [Diseño de un plan de direccionamiento estratégico para el sector piscícola] (2017)
The main purpose of this study is to design a strategic direction plan for the Trout-fish Association - ASOTRUBEL of Belmira - Antioquia, Colombia. For this purpose a systematic literature review was carried out, and 300 personalized surveys were carried out. The results describe the internal and external analysis of ASOTRUBEL, determines the variables that can affect the strategic decision making. In addition, it describes that economic and social growth is limited. Therefore, strategies are presented that could enable ASOTRUBEL to increase its sales, achieve greater presence in the market, and have an association with better development and fiscal, financial, administrative and accounting, sustainability. © 2017.